2021
DOI: 10.1038/s41598-021-94019-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics integration of methyltransferase-like protein family reveals clinical outcomes and functional signatures in human cancer

Abstract: Human methyltransferase-like (METTL) proteins transfer methyl groups to nucleic acids, proteins, lipids, and other small molecules, subsequently playing important roles in various cellular processes. In this study, we performed integrated genomic, transcriptomic, proteomic, and clinicopathological analyses of 34 METTLs in a large cohort of primary tumor and cell line data. We identified a subset of METTL genes, notably METTL1, METTL7B, and NTMT1, with high frequencies of genomic amplification and/or up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 68 publications
2
34
0
Order By: Relevance
“…METTL13 has 157 mutations annotated in the Catalog of Somatic Mutations In Cancer (COSMIC) database (Figure 7) and it has been highlighted as the most mutated METTL protein in comprehensive transcriptomics cancer datasets [63]. However, as METTL13 is a dual 7BS domain MT it is also one of the larger 7BS MTs which can represent an explanation for the high number of annotated mutations.…”
Section: Connection To Diseasesmentioning
confidence: 99%
“…METTL13 has 157 mutations annotated in the Catalog of Somatic Mutations In Cancer (COSMIC) database (Figure 7) and it has been highlighted as the most mutated METTL protein in comprehensive transcriptomics cancer datasets [63]. However, as METTL13 is a dual 7BS domain MT it is also one of the larger 7BS MTs which can represent an explanation for the high number of annotated mutations.…”
Section: Connection To Diseasesmentioning
confidence: 99%
“…METTL1 is overexpressed in glioma as compared with adjacent normal tissues and increases with increasing tumor grades. METTL1 also demonstrates a high level of genomic amplification in glioma [ 55 ]. METTL1 enhances the proliferation and growth of glioma, which may involve the tumor-related MAPK signaling pathway [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since m7G-related tumor studies are still in the preliminary stage, the remaining tumor types are grouped together in this section. Several studies have revealed upregulated expression of METTL1 in other tumors, including invasive breast carcinoma (BRCA), kidney renal clear cell carcinoma (KIRC), prostate adenocarcinoma, rectal carcinoma, and uterine corpus endometrial carcinoma [ 55 , 56 , 81 , 82 ]. Additionally, METTL1 exhibits a high level of genomic amplification in various tumors including sarcoma and adrenocortical carcinoma [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations